Geometrical assembly of ultrastable protein templates for nanomaterials - Dominic J. Glover; Lars Giger; Steve S. Kim; Rajesh R. Naik; Douglas S. Clark (Nature Communications, 2016)
Protein nanotechnology for the fabrication of protein-based nanoscale devices is gaining momentum but assembling well-defined three-dimensional shapes is still challenging. Here, the authors use an existing prefoldin assembled system to design a template for the construction of geometrically constrained structures.